2006
DOI: 10.1253/circj.70.1643
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Fluvastatin, but not at the Onset of Ischemia or Reperfusion, Attenuates Myocardial Ischemia-Reperfusion Injury Through the Nitric Oxide Pathway Rather Than Its Antioxidant Property

Abstract: arly reperfusion of an occluded coronary artery preserves myocardial viability and function by limiting the size of the myocardial infarct. 1,2 However, despite early reperfusion, myocardial ischemia-reperfusion (IR) injuries, including no reflow, stunning and reperfusion arrhythmias, sometimes occur, thereby attenuating the cardioprotective effect of reperfusion therapy. 3 Recent studies in experimental animals have demonstrated that 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
4
17
0
2
Order By: Relevance
“…heart, brain, kidney or liver (108,109). Recent studies suggested a potential implication of HMGB1 signalling in IRI (110).…”
Section: Hmgb1 In Ischemic and Reperfusion Injurymentioning
confidence: 99%
“…heart, brain, kidney or liver (108,109). Recent studies suggested a potential implication of HMGB1 signalling in IRI (110).…”
Section: Hmgb1 In Ischemic and Reperfusion Injurymentioning
confidence: 99%
“…Statins may improve endothelial function by decreasing expression of endothelial adhesion molecules, increasing nitric oxide bioavailability, and attenuating the production of reactive oxygen species. 2,21,22 In addition, statins are thought to stabilize plaque by decreasing lipid oxidation, inflammation, matrix metalloproteinase-2, and cell death and by increasing the content of tissue inhibitor of metalloproteinase-1 and collagen; these effects might reduce distal embolization. 23 Furthermore, statins have been shown to open mitochondrial adenosine triphosphate-sensitive potassium channels, suggesting pharmacological ischemic preconditioning effects.…”
Section: Statins and Myocardial Damagementioning
confidence: 99%
“…Numerous mechanisms of I/R injury have been revealed including the involvement of nitric oxide, generation of oxygen-derived free radicals, complement activation and infiltration of neutrophils into the ischemic area [5] . Most of these mechanisms will ultimately produce irreversible apoptotic injury to the myocardial tissues.…”
Section: Introductionmentioning
confidence: 99%